Orientasi Perawat Baru di Rumah Sakit dengan Sistem E-Learning - Rita Setianingrum; Santi Farida Rachmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to explain the benefits of the application of e-learning systems to new nurses in hospitals. The research design used in this study uses the literature review method. The results of young research that is 22-25 years most use E-learning with a percentage of 45.16%. Conclusions, implementation of the orientation of new nurses with the E-learning method can provide effective results. E-learning provides a variety of positive benefits for new nurses in facing work preparation in the practice field. E-learning not only provides a theoretical provision, but also provides psychological support because it can reduce the level of anxiety faced by new nurses. Keywords: Electronics, Orientation, Learning, New Nurse